Dilema petani di tengah dualisme kebijakan pertanian: Studi kasus strategi penghidupan berkelanjutan petani sawah di kawasan agropolitan Ciwidey, Jawa Barat - Nurrokhmah Rizqihandari; R. Rijanta; Sudrajat Sudrajat; Rika Harini; Hafid Setiadi (Research Centre for Population, National Research and Innovation Agency (BRIN), 2022)
Agriculture-based policies for rural development and food sufficiency lead to the welfare of farmers. However, the implementation of these policies often cannot address these issues. This study examines the impact of implementing agropolitan area and Sustainable Food Agricultural Land (LP2B) policies on paddy field farmers in the Ciwidey Agricultural Area. A review of the literature on regulations related to these two policies was conducted to identify their application in the Ciwidey area. Furthermore, a phenomenological qualitative approach was carried out to observe rice field farmers as the object of these policies. Agropolitan policies can create capital flows in agricultural areas that open opportunities to diverse farmers' livelihood portfolios. This capital inflow would be followed by activities of primitive accumulation that changed paddy field land tenure. In a strategic location, this change will increase the risk of the paddy field's conversion to non-agriculture. The LP2B policy is used to control this transfer of function. Unfortunately, the policy puts farmers with small land at risk of being in the survival strategy because their livelihood portfolio is limited. Their cultivated rice fields have less economic value compared to horticultural commodities. Although the LP2B policy can generally control land use conversion, paddy field farmers retain their identity. The primitive accumulation that follows the capital inflow due to agropolitan policy raises the risk of LP2B farmers become vulnerable in land ownership, changed from land owners to agricultural laborers. In general, this impact keeps the welfare of farmers below expectations.